Analisis Warisan Budaya : Karakteristik, Tradisi dan Keterpaduan Kehidupan Masyarakat Jawa di Kecamatan Percut Sei Tuan Kabupaten Deli Serdang Sumatera Utara - Saputri, Ayu Surya; Zega, Debora Tasya Claudia; Manik, Lolona; Tarigan, Sriwinensi; R, Rohani; Kardiana, Elsa (Madani: Jurnal Ilmiah Multidisiplin, 2025)
From the many cultures and traditions of the Javanese tribe in the area, of course, it also affects the daily lives of its people, because the place of residence of the people who mix between one tribe and another will cause a social change, one of which is the process of cultural assimilation. From the results of our research, it can be concluded that the Javanese people in the Precut Sei Tuan sub-district tend to have physical characteristics such as straight and curly black hair, brown irises, yellow to brown skin, and a non-sharp nose still hold strong Javanese traditions and culture, such as traditional customs, arts, and the use of the Javanese language. They have strong habits of mutual cooperation and family in their daily lives. Most of the Javanese people in the Percut Sei Tuan sub-district work in the agricultural sector, such as rice, vegetable, and fruit farmers. economic conditions where the main income comes from the agricultural sector and the micro-businesses that are run. Among the traditions of the Javanese people in the Precut Sei Tuan sub-district, some are still implemented, such as the 7-monthly and the joint meal event on the Islamic New Year, but most of these traditions are rarely used or no longer used on ordinary days. The blend of life between the Javanese people and local culture in the Percut Sei Tuan sub-district reflects the dynamic process of cultural assimilation and acculturation. Both cultures influence and enrich each other, creating their own uniqueness in the lives of the people in the area.